Ductile tearing simulation of STS410 pipe fracture test under load-controlled large-amplitude cyclic loading: Part I—Effect of load ratio. (1st March 2020) - Hwang, Jin-Ha; Youn, Gyo-Geun; Kim, Hune-Tae; Kim, Yun-Jae; Miura, Naoki
Highlights: Ductile tearing simulation under cyclic loading is compared with of STS410 pipe test. Cracked pipe test is performed under large-amplitude load-controlled cyclic loading. Cyclic loading consists of three different load ratios with the same maximum load. FE simulation using a multi-axial fracture strain energy damage model is performed. The damage model is determined from tensile test and one monotonic loading pipe test. The effect of the cyclic hardening model on cyclic loading simulation is discussed. Abstract: Ductile fracture of circumferential through-wall cracked pipe under large-amplitude load-controlled cyclic loading with three different load ratios was simulated using a fracture strain energy damage model. Damage model parameters were determined from a tensile test and a pipe test under monotonic loading. Comparison of simulated and experimental data reveals that the simulation results depend on the cyclic hardening model. Further investigation confirmed that selection of an appropriate cyclic hardening model is more important under load-controlled cyclic loading then under displacement-controlled one.